2022
DOI: 10.1002/adfm.202209142
|View full text |Cite
|
Sign up to set email alerts
|

Self‐driven Electrical Stimulation Promotes Cancer Catalytic Therapy Based on Fully Conjugated Covalent Organic Framework Nanocages

Abstract: Engineered nanozymes have been developed to catalyze the production of reactive oxygen species (ROS) for cancer therapy, but currently, the ROS generation efficiency is still far from optimistic. In this study, a human self‐driven electrical stimulation enhanced catalytic system based on wearable triboelectric nanogenerator (TENG) and fully π‐conjugated covalent organic framework nanocages (hCOF) for improving cancer therapy is created. The fully π‐conjugated hCOF nanocage with high electron mobility under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…However, the poor light penetration ability of these catalysts severely limits the activity enhancement. 7 Similar to its effect on natural protein enzymes, using external electrical stimulation to modulate the electrostatic field can also improve the catalytic activity of nanozymes. 8 However, electrical stimulation often requires the use of high current and large equipment because the external electric fields cannot precisely target the nanozymes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the poor light penetration ability of these catalysts severely limits the activity enhancement. 7 Similar to its effect on natural protein enzymes, using external electrical stimulation to modulate the electrostatic field can also improve the catalytic activity of nanozymes. 8 However, electrical stimulation often requires the use of high current and large equipment because the external electric fields cannot precisely target the nanozymes.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that TME is weakly acidic (pH 6.2–6.8) with a high concentration of H 2 O 2 . According to our recent research studies, the self-powered electric field can promote cancer catalytic therapy through modulation of electron polarization and electron transfer in nanozyme. , To investigate the influence of TENG-enabled electric field on the catalytic properties, we designed a series of experiments (Figure a). It should be mentioned that to exclude the influence from optical absorption of the released DOX, CN-F was used in these experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to conventional power sources, triboelectric nanogenerators (TENGs) as a self-powered electrical source can efficiently convert the mechanical energy of ambient human motions into electrical pulses without the need for external energy supply, breaking through the time and space limitations of traditional equipment. In our recent studies, we have also demonstrated that the TENG-enabled electric field stimulation can promote the catalytic therapy of cancer by generating free radicals. , Moreover, it was reported that the TENG-based therapeutic platforms can assist delivery of therapeutic agents to the disease site through electrical stimulation. , Therefore, TENGs have great potential for application in cancer treatments through the self-powered manner and portable or wearable devices. For this target, how to efficiently deliver electrical stimulation to local tumor tissues is still a great challenge.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations